An unexpected case of Castleman disease in porta hepatis lymphadenopathy. Issue 4 (22nd April 2023) - Li, Crystal; Hameed, Ahmer; Pleass, Henry
Abstract: Castleman disease (CD) is a rare lymphoproliferative disorder that can be life threatening if left unmanaged in severe cases of inflammatory response. CD should be excluded by thorough workup in cases of lymphadenopathy and splenomegaly of unknown cause. Excisional biopsy of lymph nodes may be required to make a definitive diagnosis. A case of CD manifesting as portal hepatis lymphadenopathy is presented.